2015
DOI: 10.1149/06803.0117ecst
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Impedance Spectroscopy Study and Two Phase Flow Analysis of the Anode of Polymer Electrolyte Membrane Water Electrolyser

Abstract: The effect of water flow rate on the performance of a polymer electrolyte membrane water electrolyser (PEMWE) was studied using an unpressurised lab-scale (25 cm 2 ) cell. The linear polarisation curves obtained showed a voltage increase at higher current densities that increased with water flow rate. Electrochemical impedance spectroscopy (EIS) showed that while lower water flow rates lead to higher cell temperatures and reduced membrane resistance, mass transport losses dominate at high current density. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The electrochemical impedance of the electrolyzer cell was recorded at the start of the experiment, as shown in Fig. 1(a), using an equivalent circuit; an inductance was added to the equivalent circuit due to external cablings and connections [35,36]. Impedance was measured at a DC bias of 1.80 V (from 100 kHz to 100 mHz).…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical impedance of the electrolyzer cell was recorded at the start of the experiment, as shown in Fig. 1(a), using an equivalent circuit; an inductance was added to the equivalent circuit due to external cablings and connections [35,36]. Impedance was measured at a DC bias of 1.80 V (from 100 kHz to 100 mHz).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that transition from bubbly to slug flow and bigger bubbles (based on whole cell analysis) enhance mass transport (bubble removal and water access to the electrode) in an electrolyser and hence results in better performance [42,[44][45][46][47]. Figure 6 shows that the gas void fraction in the flow channels increase with operating potential and decreasing water flow rate.…”
Section: Visual Imaging Of Bubble Size and Two-phase Flow Patternsmentioning
confidence: 90%
“…Figure 6 shows that the gas void fraction in the flow channels increase with operating potential and decreasing water flow rate. Our previous study discusses the influence of the void fraction on the mass transport coefficient, which states the it has an inverse relationship [47,48].…”
Section: Visual Imaging Of Bubble Size and Two-phase Flow Patternsmentioning
confidence: 99%
“…Compared to the bulk properties of the PTL, the structure at the ACL/PTL interface appears to dominate the utilization of the ACL and, therefore, the achievable performance of the PEMWE cell. 12,18 The major published PEMWE models are 0-D [22][23][24][25][26][27][28][29][30][31] and 1-D 2,32-36 and investigate the change of cell variables in through-plane (i.e., perpendicular to the layered structure of the cell) direction. Within the group of 1-D models, most focus on investigating the mass transport behavior within the PTL structure.…”
Section: List Of Symbolsmentioning
confidence: 99%